PERANCANGAN SISTEM INFORMASI PENGELOLAAN STOK DAN PENJUALAN ALAT TULIS KANTOR PADA TOKO ANUGERAH JAYA - Tirto; Sudirman; Afifah (JTRISTE, 2018)
This study aims to design a system that can assist the Toko Anugerah Jaya in managing the stock and sales of stationery, where the stock management using the method of Average. To obtain data and information that support the implementation of this research, conducted observations and interviews. Information Systems Stock control is designed using Data Flow Diagrams (DFD), then implemented using Visual Basic 6.0 and Microsoft Access programming as a data processor, then tested using the Black Box testing method. With the new computer-based system is expected to store owners Toko Anugerah Jaya can run the process of stock management and sales of office supplies.